SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI MADRASAH ALIYAH NEGERI 2 KOTA KEDIRI - Arofatul Kiptiyah (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
In improving professional competence, it is strongly influenced by the role of the principal as a supervisor through academic supervision. This study aims to determine the planning of the madrasah principal's academic supervision program, the implementation of the madrasah's academic supervision, and the follow-up to the results of the madrasah's academic supervision in improving the professional competence of teachers. With academic supervision, it is expected to provide technical assistance, guidance, coaching and performance improvement as an effort to improve the professional competence of teachers so that they can achieve educational goals. This study uses a qualitative approach. Data collection techniques through observation, interviews, and documentation. The subjects of this study were the principal and teachers. The results of the study show that: (1) the preparation of the academic supervision program is prepared at the beginning of the new school year by involving teachers. The academic supervision program is structured based on problems faced by teachers regarding learning and adapts to the needs of teachers; (2) the implementation of academic supervision in accordance with the program that has been prepared using several supervision techniques including individual and group techniques; and (3) Follow-up actions taken by the head of the madrasa by providing guidance to teachers.